FEE BASED INCOME SEBAGAI DETERMINAN PROFITABILITAS: BUKTI EMPIRIS PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putri Tyas Permatasari; Yuli Surya Fauzia Pertami; Rima Dwijayanty; Indri Gustirani (Universitas Sangga Buana, 2026)
This study is motivated by fluctuations in banking profitability caused by uncertainty in interest income, encouraging banks to optimize non-interest income through Fee Based Income (FBI). The study aims to examine the effect of Fee Based Income on profitability, measured by Return on Assets (ROA), in conventional commercial banks listed on the Indonesia Stock Exchange during 2019–2023. A quantitative approach with an associative research method was employed. Using purposive sampling, the study obtained 24 banks with 105 observations after outlier elimination. The data were analyzed using panel data regression with the Random Effect Model (REM). The findings reveal that Fee Based Income has a positive and significant effect on ROA. These results indicate that increasing non-interest income enhances bank profitability and strengthens financial performance resilience through income diversification.